Biopesticide Application Of Bacillus thuringiensis Local Isolate To Control Atherigona exigua Pest On Corn Plants - Christina Leta Salaki; Jackson Watung (Jurnal Agroekoteknologi Terapan, 2022)
Atherigona exigua is one of the main plant pest organisms (OPT) in maize. Among these pest control alternatives, the use of Bacillus thuringiensis bacteria has received attention because of its efficiency and low impact on natural enemies. This study aims: (1) to obtain the concentration of B. thuringiensis which has a high killing power on mortality of A. exigua larvae, (2) to determine the pathogenicity of B. thuringiensis to A. exigua. Testing for killing power and pathogenicity used the "Leaf dipped method" with five different concentrations of bacterial spore suspension, namely 1.5 x 103, 1.5 x104, 1.5 x 105, 1.5 x 106 and 1.5 x 107 spores/ml. . Parameters observed included attack symptoms, mortality percentage and time of death. Larval mortality was observed at 12, 24, 48 and 72 hours after application. Pathogenicity values ​​were expressed by LC50 and LT50 using probit analysis. The results showed that testing the killing power of 24 isolates, there were 10 isolates that were able to kill A. exigua larvae 50% after 72 hours at a concentration of 1.5 x 107 spores/ml, while the pathogenicity test based on the results of probit analysis showed that ITH isolates had a positive value. LC50 = 7.5 x 103 spores/ml. Time of death (LT50) = 19.5 hours. Keywords: OPT, Concentration, Leaf dipped method, pathogenicity. Abstrak Atherigona exigua merupakan salah satu organisme pengganggu tanaman (OPT) utama pada tanaman jagung. Di antara alternatif pengendalian hama ini, penggunaan bakteri Bacillus thuringiensis mendapat perhatian karena efisiensinya dan dampaknya yang rendah terhadap musuh alami. Penelitian ini bertujuan : (1) Mendapatkan konsentrasi B. thuringiensis yang mempunyai daya bunuh yang tinggi terhadap mortalitas larva A. exigua, (2) Mengetahui patogenisitas B. thuringiensis terhadap A. exigua. Pengujian daya bunuh dan patogenisitasnya menggunakan metode “Leaf dipped method” dengan lima macam konsentrasi suspense spora bakteri yaitu 1,5 x 103, 1,5 x104, 1,5x 105, 1,5 x 106 dan 1,5 x 107 spora/ml. Parameter yang diamati meliputi gejala serangan, persentase mortalitas dan waktu kematian. Mortalitas larva diamati pada 12, 24, 48 dan 72 jam setelah aplikasi. Nilai patogenisitas dinyatakan dengan LC50 dan LT50 dengan menggunakan analisis probit. Hasil penelitian menunjukkan bahwa pengujian daya bunuh dari 24 isolat, terdapat 10 isolat yang dapat mematikan larva A. exigua ≥ 50 % setelah 72 jam pada konsentrasi 1,5 x 107 spora/ml, sedangkan uji patogenisitas berdasarkan hasil analisis probit menunjukkan isolat ITH mempunyai nilai LC50 = 7,5 x 103 spora/ml. Waktu kematian (LT50) = 19,5 jam. Kata Kunci : OPT, Konsentrasi, Leaf dipped method, patogenisitas